ANALISIS KEMAMPUAN BERPIKIR KOMPUTASI MAHASISWA DALAM PEMBUKTIAN INDUKSI MATEMATIKA - Syahlan, Syahlan; Siregar, Rosliana; Malay, Irval (MES: Journal of Mathematics Education and Science, 2023)
The increasingly rapid development of technology and information has enabled transformation in the fields of education and teaching. This is clearly seen in the current curriculum expectations, where one of the expected learning outcomes from elementary school to middle school is that students are expected to have computational thinking skills. For this reason, the aim of this research is to look at students' abilities related to their computational thinking abilities. in solving the problems given. The results of the answers given by students are then analyzed according to the four foundations of computational thinking. This research is descriptive research with a qualitative approach. This research was carried out in the Mathematics Education study program, Universitas Islam Sumatera Utara in the Number Theory course. The sample used was 12 students taking Number Theory courses. The instrument used is a description of 2 questions which are given during the learning process on mathematical induction material. The students' answer sheets were then analyzed to get a picture of students' computational thinking abilities based on the four foundations. The results of this research show that students' computational thinking abilities still need to be improved, such as decomposition abilities which are 41.67% and abstraction abilities which are 58.33%. Overall, students' computational thinking abilities are still in the sufficient ability category.